Secret princess for the warrior - Styles, Michelle (Harlequin historicals., 2025)
"When Viking Karn finds himself shipwrecked on enemy territory, even his razor-sharp, battle-hardened instincts could never have foreseen being rescued by tantalizing maiden Maer... Maer is stunned to learn that Karn hails from the kingdom that was once her home. And that his father was responsible for the brutal end to her family's reign, forcing Maer to become a princess-in-hiding! She should hate Karn but instead finds herself irresistibly drawn to the brooding warrior. He could be the key to her return, but can she trust him with her feelings-and her royal secret?" --